2015
DOI: 10.1111/1467-856x.12065
|View full text |Cite
|
Sign up to set email alerts
|

Capturing Desire: Rhetorical Strategies and the Affectivity of Discourse

Abstract: This article:• Provides a theoretical exploration of rhetorical persuasion as a practice aimed at 'capturing desire'. • Elucidates the shared interest of rhetorical and psychoanalytical theory in the production of so-called 'plausible stories' that mobilise and shape affects. • Surveys different psychoanalytical approaches to the rhetorical articulation of 'symptomatic beliefs' that support political reasoning. • Demonstrates the applicability of psychoanalytical theories to the analysis of a specific example … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…The present article begins to address this oversight, and so will make a contribution to scholarship on both Britishness and British political speech (e.g. Atkins, 2011;Atkins and Finlayson, 2014;Finlayson, 2014;Martin, 2015).…”
Section: National Identitymentioning
confidence: 99%
“…The present article begins to address this oversight, and so will make a contribution to scholarship on both Britishness and British political speech (e.g. Atkins, 2011;Atkins and Finlayson, 2014;Finlayson, 2014;Martin, 2015).…”
Section: National Identitymentioning
confidence: 99%
“…And this in turn opens up an interesting research pathway, calling for a theoretical and speculative comparative inquiry into how fantasy and other psychoanalytic categories can produce revealing insights when juxtaposed to, and contrasted with, other key categories drawing on other traditions: reification, fetishism, structures of feeling, rhetoric, myth, narrative, metaphor, utopia, and so on. Rhetoric, to take just one example, appears to be a promising concept for such a comparative exploration, particularly as elaborated by scholars such as Alan Finlayson (2012) and James Martin (2014;2016). At least two features of their work are worth commenting on.…”
Section: Questions Of Theory: Fantasy and Enjoymentmentioning
confidence: 99%
“…First, their brand of 'rhetorical political analysis' already constitutes a reactivation and deconstruction of classical rhetorical categories, rearticulating them in a way that is compatible with basic poststructuralist presuppositions and thus directly pertinent for post-Marxist discourse theory scholars. In addition, however, recent work has suggested conceptualizing rhetorical persuasion also as a way of 'capturing desire' (Martin 2016). This opens up a terrain rich for further comparative-conceptual investigation within the field of critical fantasy studies.…”
Section: Questions Of Theory: Fantasy and Enjoymentmentioning
confidence: 99%
“…According to Nelson, Megill and McCloskey (1987), since rhetoric has the power to influence cultural and political affairs, scholars as far back as Ancient Greece and throughout history have studied it as a predominately consciously and deliberately induced phenomenon. From this perspective, writers suggested various definitions for rhetoric, such as the art of persuasion, the affective and motivating aspects of speech intertwined with its logical and factual aspects (Martin, 2016), the ways of effectively using spoken or written language to inform and persuade others (Bizzell & Herzberg, 2001), and ways of intensely conveying narrators’ experiences (Skelton, 2006). Senn (2017) also suggested that people use rhetorical devices to persuade others of their natural authority and fidelity to historical facts or conventional beliefs and that the issues spoken about are profoundly meaningful for the listeners’ interests.…”
Section: Rhetorical Devicesmentioning
confidence: 99%